Phase II randomised study of maintenance treatment with bevacizumab or bevacizumab plus metronomic chemotherapy after first-line induction with FOLFOXIRI plus Bevacizumab for metastatic colorectal cancer patients: the MOMA trial. (March 2019) - Cremolini, Chiara; Marmorino, Federica; Bergamo, Francesca; Aprile, Giuseppe; Salvatore, Lisa; Masi, Gianluca; Dell'Aquila, Emanuela; Antoniotti, Carlotta; Murgioni, Sabina; Allegrini, Giacomo; Borelli, Beatrice; Gemma, Donatello; et al.
Abstract: Background: Alternating induction and maintenance phases is a common strategy in metastatic colorectal cancer (mCRC). Metronomic chemotherapy (metroCT) may represent a well-tolerated chemotherapy backbone for maximising bevacizumab effect during maintenance. The MOMA trial was designed to compare metroCT plus bevacizumab versus bevacizumab alone as maintenance following 4 months of induction with FOLFOXIRI plus bevacizumab. Patients and methods: In this phase II study, patients with unresectable mCRC were randomised to receive up to 8 cycles of FOLFOXIRI plus bevacizumab, followed by bevacizumab (arm A) or the same regimen followed by bevacizumab plus metroCT (capecitabine 500 mg/three times per day and cyclophosphamide 50 mg/die, arm B) until disease progression. The primary end-point was progression-free survival (PFS). According to the Rubinstein and Korn's design, to detect a hazard ratio[HR] of 0.75 favouring arm B, with 1 sided-alpha and beta errors of 15% and 80%, 173 events and 222 patients were required. Results: Between May 2012 and March 2015, 232 patients, mostly with RAS (65%) or BRAF (9%) mutant tumours, were randomised in 16 Italian centres. At a median follow-up of 47.8 months, 210 and 164 progression and death events were registered. The primary end-point was not met. Median PFS was 10.3 and 9.4 months in arm B and A, respectively (HR: 0.94 [70% confidence interval CI: 0.82–1.09], p = 0.680). No significant differences were reported in terms of overall survival (OS) (median OS arm B/A: 22.5/28 months; HR: 1.16 [95%CI: 0.99–1.37], p = 0.336). Response rate with FOLFOXIRI plus bevacizumab was 63% (arm B/A: 58%/68%). In the liver-limited subgroup, the secondary resection rate was 49% (arm B/A: 45%/55%). Conclusions: The addition of metroCT to maintenance with bevacizumab does not significantly improve PFS of mCRC patients. The activity of FOLFOXIRI plus bevacizumab is confirmed in a population with high prevalence of RAS/BRAF mutations treated with a 4-months induction. Trial registration: www.clinicaltrials.gov NCT02271464. Highlights: The addition of metronomic chemotherapy to bevacizumab (bev) during maintenance does not significantly improve PFS. 5FU/bev is the standard maintenance following upfront FOLFOXIRI/bev. The activity of FOLFOXIRI/bev is confirmed with 4 instead of 6 months duration. Results among BRAF mutants are consistent with previous findings with FOLFOXIRI/bev.